Household’s willingness to pay for watershed protection services in Langat Basin, Selangor using contingent valuation method - Devika Krishnan,; Shaharuddin Mohamad Ismail,; Sara Kaffashi,; Siwar Chamhuri,; Faten Naseha,; Pushpawani Ramloo, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
The significance of having a payment scheme for ecosystem services (PES) for the purpose of watershed protection in order to develop a sustainable forest management is globally recognised. PES is an advanced financial tool to foster a platform for generating a source of income from ecosystem service users to ecosystem providers. More importantly, the involvement of households is vital for the successful implementation of PES programmes. Thus, this study aims to examine the willingness to pay for watershed protection services among households in the Langat Basin. Households around upstream, middle-stream and downstream segments of the Langat Basin were selected randomly to be studied and involved in face-to-face interviews. The Probit and Logit models in Contingent Valuation Method (CVM) were employed to assess household’s WTP towards watershed protection efforts of the Langat Basin. The mean for WTP of Upstream household is RM30.01 while middle-stream household’s WTP is RM33.07 compared to that of the downstream household, which is RM32.41. The households’ WTP shows an increasing trend from upstream to downstream households. These results offer a new insight and discernment between PES programmes and households’ WTP so as to develop a sustainable management for water-based ecosystem services.